Itch! : everything you didn't want to know about what makes you scratch - Sanchez, Anita, 1956-; Ford, Gilbert (Boston : Houghton Mifflin Harcourt, 2018)
Everybody gets itchy, and every kid will love this title that scratches the itch to know more and about the history, anatomy, botany, biology behind it.
Skin! a bag with you inside -- Lice! scratching through the centuries -- Flea! welcome to the circus -- Plants! the green world fights back -- Mosquito! why they love to bite us -- Tarantula! remember me -- Fungus! the invisible itch -- Bedbugs! learning a smelly language -- Itching? is there anything good about itching?
Elementary Grade.
960
Accelerated Reader.
Reading Counts!
Includes bibliographical references and index.
Accelerated Reader AR
Keywords: Itching -- Juvenile literature; Skin -- Diseases -- Juvenile literature; Poisonous animals -- Juvenile literature; Poisonous plants -- Juvenile literature; Itching -- Juvenile literature; Pruritus; Itching; Poisonous animals; Poisonous plants; Skin -- Diseases; Skin -- Diseases; Poisonous animals; Poisonous plants; Instructional and educational works; Juvenile works; Instructional and educational works